The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1063/1.105092
|View full text |Cite
|
Sign up to set email alerts
|

Clear correlations observed between YBa2Cu3O7−δ thin-film properties and GHz microwave resonator performance

Abstract: We have fabricated and measured 5 GHz microstrip resonators from a series of YBa2Cu3O7−δ thin films grown on LaAlO3(001) substrates by in situ laser ablation. We have studied the correlations between unloaded quality factor and various film properties, such as transition temperature, width of transition, critical current density, narrowness of x-ray rocking curve, sharpness of electron channeling pattern, and most important substrate temperature during growth. We found that in general, higher transition temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Continued miniaturization of integrated circuitry requires microwave components with improved characteristics, smaller size, and compatibility with existing circuits. [1][2][3][4] Generally, dielectric materials used for resonators and filters in microwave circuits must exhibit high dielectric constants ͑because the resonator size is proportional to 1/ͱ), low dielectric losses (tan ␦ϭ1/Q, where Q is the dielectric quality factor͒, and low temperature coefficients of resonance frequency ( f ). 5 It has been reported that the bulk ZrTiO 4 phase has a high dielectric constant suitable for microwave devices, a low dielectric loss, and good thermal stability with Sn addition.…”
Section: ͓S0003-6951͑00͒04521-6͔mentioning
confidence: 99%
“…Continued miniaturization of integrated circuitry requires microwave components with improved characteristics, smaller size, and compatibility with existing circuits. [1][2][3][4] Generally, dielectric materials used for resonators and filters in microwave circuits must exhibit high dielectric constants ͑because the resonator size is proportional to 1/ͱ), low dielectric losses (tan ␦ϭ1/Q, where Q is the dielectric quality factor͒, and low temperature coefficients of resonance frequency ( f ). 5 It has been reported that the bulk ZrTiO 4 phase has a high dielectric constant suitable for microwave devices, a low dielectric loss, and good thermal stability with Sn addition.…”
Section: ͓S0003-6951͑00͒04521-6͔mentioning
confidence: 99%
“…For miniaturization of integrated circuitry, microwave dielectric components need improved characteristics, smaller size, and compatibility with existing circuits. [1][2][3][4] Paraelectric materials used as resonators and filters in microwave circuits require high dielectric constants (resonator size proportional to 1/ √ ε), low dielectric losses (tan δ), and low temperature coefficients of resonance frequency (τ f ).…”
Section: Introductionmentioning
confidence: 99%
“…Passive microwave components such as resonators [l], [2] and filters [3], [4] are promising applications of high-Tc superconductors (HTS) because they have significantly lower microwave surface resistance (Rs) than normal metals. In practical applications, the power handling capability of HTS films is also important, as well as with low loss.…”
Section: Introduci~onmentioning
confidence: 99%